Comparative field evaluation of kelambu traps, barrier screens and barrier screens with eaves for longitudinal surveillance of adult Anopheles mosquitoes in Sulawesi, Indonesia - Jenna R. Davidson; Isra Wahid; Rusdiyah Sudirman; Victoria Makuru; Hajar Hasan; Andi Muhammad Arfah; Nirwana Nur; Muhammad Yusuf Hidayat; Allison L. Hendershot; Honglin Xiao; Xiaoyu Yu; Puji Budi Setia Asih; et al. (Parasites & Vectors, 2019)
Abstract Background Sampling methodologies for mosquitoes that are capable of transmitting vector-borne infectious diseases provide critical information on entomological endpoints. Reliable and meaningful field data is vital to the understanding of basic vector biology as well as disease transmission. Various traps take advantage of different vector behaviors and are inevitably subject to sampling biases. This study represents the first comparison of kelambu traps (KT) to barrier screens (BS), barrier screens with eaves (BSE) and indoor and outdoor human landing catches (HLCs). Methods Two trap comparison studies were undertaken. In the first study, mosquitoes were collected in Karama over 26 trapping nights to evaluate the kelambu trap relative to indoor and outdoor HLCs. In the second study, mosquitoes were collected in Karama over 12 trapping nights to compare the kelambu trap, barrier screen, barrier screen with eaves and outdoor HLCs. The kelambu trap, barrier screen and barrier screen with eaves obstruct the flight of mosquitos. HLCs target host-seeking behaviors. Results There was no significant difference between indoor and outdoor HLCs for overall Anopheles mosquito abundance. All five of the molecularly identified Anopheles species collected by HLCs, An. aconitus, An. barbirostris, An. peditaeniatus, An. vagus and An. tessellatus, are reported as vectors of malaria in Indonesia. The kelambu trap (n = 2736) collected significantly more Anopheles mosquitoes than indoor HLCs (n = 1286; Z = 3.193, P = 0.004), but not the outdoor HLCs (n = 1580; Z = 2.325, P = 0.053). All traps collected statistically similar abundances for the primary species, An. barbirostris. However, both comparison studies found significantly higher abundances for the kelambu trap for several secondary species compared to all other traps: An. nigerriumus, An. parangensis, An. tessellatus and An. vagus. The kelambu trap retained the highest species richness and Gini-Simpson’s diversity index for both comparison studies. Conclusions This study demonstrates that the kelambu trap collects overall Anopheles abundance and species-specific abundances at statistically similar or higher rates than HLCs in Sulawesi, Indonesia. Therefore, the kelambu trap should be considered as an exposure-free alternative to HLCs for research questions regarding Anopheles species in this malaria endemic region.